(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Tourism is a significant contributor to global economic development, with small business entities (SBEs) playing a critical role in supporting tourism growth. This paper explores the economic importance of tourism development through SBEs by analyzing their contribution to GDP, employment, and local development. Using mixed methods, data were collected from specific region or country, focusing on the impact of SBEs in the tourism sector. Results indicate that SBEs contribute significantly to GDP, accounting for specific percentage of tourismrelated income and creating specific number jobs. Furthermore, SBEs foster sustainable tourism and drive inclusive development in underserved regions. The study concludes with policy recommendations for enhancing the role of SBEs in tourism.